A mail survey approach to watershed condition assessment - Lomnicky, G. A.; Barker, J. R.; Bryce, S. A. (Journal of soil and water conservation, 2002)
Aquatic resource monitoring attempts to assess the condition of aquatic habitat and organisms. Assessments require that disturbances from human activities be identified, quantified and ordered along a gradient for interpreting biological response. An index of relative risk to aquatic systems was developed based on identifying and prioritizing stream-reach and watershed stressors. Mail surveys were sent to natural resource experts (county extension agents, NRCS employees) familiar with the targeted watersheds, to collect data for assessment of 25 watersheds in the Mid-Appalachian region of the United States. A 56% correspondence was found between this method and another approach when scoring identical sites. Scoring differences resulted from discrepancies in available data between the two methods. Scores were consistent with water chemistry and benthic macro invertebrate measures of stream condition and required less time to develop for ranking watersheds than the second method. The mail survey approach is readily transferable to other regions.